PENGGUNAAN APLIKASI QUIZLET DALAM PEMBELAJARAN KANJI PADA MAHASISWA ANGKATAN 2021 - Ahmad Dani; Nana Rahayu; Adisthi Martha Yohani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study aims to know the different before and after using Quizlet app in kanji subject. This study conducted with pre-experimental research method with One-Group Pretest-Posttest design. The sample in this study is 2021 class student of Japanese Language Education Study Program B group with total 17 students. Instrument in this study used a test. The result of this study indicated that Quizlet app have significant influence for enchanting leaner’s kanji acquisition ability. Even so, from 17 students there are 2 students that didn’t get improved and 1 student have experienced decrease in value after using Quizlet appKey Word : Learning Media, Kanji, Quizlet